A contingency view on the impact of supplier development on design and conformance quality performance. Issue 4 (12th March 2017) - Salimian, Hamid; Rashidirad, Mona; Soltani, Ebrahim
Abstract: This study extends contingency theory's account of organisational size and culture by exploring the relationship between supplier development and internal quality performance. Drawing on supplier development research, the study aims to examine the moderating impact of organisational size and culture on the relationship between supplier development and design and conformance quality dimensions. Using survey data of 518 UK manufacturing organisations, we found that larger organisations with greater access to resources and a strong supply chain orientation culture tend to place the most weight on supplier development programmes which in turn yield higher internal quality performance. These findings contribute to 'Operations Management Practice Contingency Research (OM PCR)' and will raise awareness among operations managers of their future sourcing decisions.